Study on types of Leaf Chlorosis in Kinnow Mandarin (Citrus reticulata Blanco) under rainfed condition - KUMAR, VIJAY; KUMAR, MANOJ (Journal of Soil and Water Conservation, 2024)
Nutrient management is the main causes of worse productivity and decline of Kinnow mandarin orchards. The soil and leaf nutrients study were observed in three fruit growing orchards viz: healthy non-fruiting orchard, healthy fruiting orchard and declining orchard in subtropics region of Jammu. The available nutrients of soil were decreased with increased soil depth as well as bulk density and soil pH was reverse trends. The healthy fruiting orchard was higher in soil organic carbon (3.96 g kg-1) and available major-nutrients of N, P, K, S i.e. 278.43 Kg ha-1, 14.78 Kg ha-1, 178.36 Kg ha-1 and 2.57 mg kg-1, respectively. The DPTA extractable micronutrient Fe, Mn, Zn and Cu i.e. 16.26 mg kg-1, 2.18 mg kg-1, 2.82 mg kg-1 and 1.12 mg kg-1, respectively were also observed in healthy fruiting orchards. The leaves like major and minor nutrients were higher in healthy fruiting orchard followed by healthy non-fruiting orchard and declining orchard in this region.